User Persona Clustering to Enhance Digital Marketing Strategy in Bakrie University - Handayani, Widya; Reynaldi, Jaka; Chairani, Metha Erzha; Heikal, Jerry (Asean International Journal of Business, 2025)
This research describes the Clustering of User Personas on the Digital Marketing Strategy of Bakrie University. In carrying out the testing of this algorithm, the data used is sample data from Bakrie University students. In this application, the application of clustering using the K-means algorithm is used. In the results of this study, Bakrie University can do effective digital marketing using social media Instagram.The Industrial Revolution 4.0 has transformed technology and education, pushing institutions to adopt innovative marketing strategies. This study focuses on Bakrie University's digital marketing efforts using the K-Means clustering method to analyze student personas. Data from 100 students revealed three distinct clusters based on demographics, social media usage, and preferences. Cluster 1 (younger group) favored Instagram and YouTube, Cluster 2 relied heavily on Instagram, and Cluster 3 (older group) used a mix of Instagram, YouTube, and Facebook. On average, users across all clusters spent 4-8 hours daily on social media, emphasizing its significance in marketing. The study concludes that Instagram is the most effective platform for engaging all clusters, with YouTube serving as a supplementary tool. These insights demonstrate how clustering analysis can help educational institutions develop targeted, data-driven strategies to strengthen their brand, attract students, and enhance their competitiveness in the digital era.